Role of Taurine in Male Reproductive System Performance in Adult Male Rats Exposed to Oxiative Stress by Hydrogen Peroxide - Nadhem Ahmad Hassan Al-kassim (Journal of Applied Veterinary Sciences, 2019)
The experiment has been conducted to study the role of taurine of the concentration (0.5 & 1%) in the performance of the male reproductive system of rats that are exposed to oxidative stress by hydrogen peroxide for six weeks. 32 albino adult male rats aged (12-14) weeks and weighing (252.3 +/- 27.08 gram), divided into four groups: Control Group:- this group is given natural water. Group (2): treated with (H2O2, 0.5%) in drinking water. Group (3): treated with (H2O2, 0.5%) by taurine (0.5%) in drinking water. Group (4): treated with (H2O2, 0.5%) by taurine (1%) in drinking water. The results reveal that this exposure with (0.5 % H2O2) has led to an significant decrease in the body weight and the ano – genital distance, the percentage weight of the testicles, head and tail of eqididymis, prostate gland, seminal vesicles, the percentage of live sperms, the number of Legdig and Sertoli cells, as well as the significant increase in the percentage of abnormal sperms and an significant decrease in the diameter of seminiferous tubules. Treatment with taurine (0.5 & 1%) has led to an significant improvement in the body weight, ano-genital distance, the percentage of the testicles weight, head and tail of eqididymis, prostate gland, seminal vesicles, the percentage of live sperms, the number of Legdig and Sertoli cells, as well as the significant decrease in the percentage of abnormal sperms and an significant increase in the diameter of seminiferous tubules in comparison with the treatment group by hydrogen peroxide. Treatment with taurine (1%) has led to an significant improvement of the sperm count and the percentage weight of the head and tail of the epididymis as well as the number of Legdig and Sertoli cells compared with the control group and the group of taurine (0.5%).